The Causes of Persistent and Recurrent Nasal Obstruction After Primary Septoplasty. Issue 4 (June 2016) - Derin, Serhan; Sahan, Murat; Deveer, Mehmet; Erdogan, Selvet; Tetiker, Hasan; Koseoglu, Sabri
Abstract : Objectives: Septoplasty is the most frequently performed surgical procedure in patients with nasal obstruction. However, nasal obstruction may persist or recur after septoplasty in some patients. In this study, the authors aimed to determine the causes of nasal obstruction after septoplasty. Methods: Fifty consecutive patients who admitted to our clinic with the complaints of persistent or recurrent nasal obstruction after primary septoplasty and had revision surgery between 2011 and 2015 were included in this study. Demographic data and physical examination findings of the patients were recorded. Results: There were 33 men (66%) and 17 women (34%) with a mean age of 37.3 ± 10.5 (range, 21–57) years. Deviation of perpendicular plate of ethmoid bone (44%), inferior turbinate hypertrophy (36%), concha bullosa (26%), caudal septal deviation-nostril asymmetry (20%), and alar collapse (6%) were the pathologies that were unaddressed during primary surgery. The iatrogenic causes of nasal obstruction after septoplasty were collumellar retraction–nasal tip ptosis (46%), nasal synechiae (20%), nasal septal perforation (10%), and saddle-nose/flat nose deformity (10%). Conclusions: Iatrogenic deformities due to surgery and pathologies ignored during primary surgery may cause persistent/recurrent nasal obstruction after primary septoplasty. A detailed physical examination and objective tests showing the site of nasal obstruction, an extensive surgical plan that covers all diagnosed pathologies, and a careful postoperative care must be undertaken to prevent undesired postoperative results.